1995
DOI: 10.1203/00006450-199507000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin Effects on Lung Liquid Volume in Fetal Sheep

Abstract: The normal switch from placental to pulmonary gas exchange at birth requires rapid removal of liquid from the lungs. Previous reports contend that vasopressin may be important in regulating this process, but this notion derives from studies in which fetal sheep received very large doses of vasopressin that yielded plasma concentrations at least 10 times greater than those that have been measured during normal labor. To study the physiologic effects of vasopressin on lung liquid volume in fetal sheep, we made t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 40 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…Compared to vaginal delivery, infants delivered by cesarean section have a significantly increased risk of neonatal admission because of respiratory complications mainly due to delayed lung fluid reabsorption after birth, namely wet lung ( 121 ). AVP has been shown to decrease the production of fetal lung liquid in ovine fetuses ( 122 ), and it has been shown that AVP is involved in liquid removal from the lungs at birth ( 123 125 ). Thus, it might be speculated that, in the absence of preconditioning, when primary cesarean section was performed, AVP administration shortly after birth to the baby, e.g., via nasal spray, might represent a novel strategy to support postnatal adaptation.…”
Section: Avp In Healthy Neonatesmentioning
confidence: 99%
“…Compared to vaginal delivery, infants delivered by cesarean section have a significantly increased risk of neonatal admission because of respiratory complications mainly due to delayed lung fluid reabsorption after birth, namely wet lung ( 121 ). AVP has been shown to decrease the production of fetal lung liquid in ovine fetuses ( 122 ), and it has been shown that AVP is involved in liquid removal from the lungs at birth ( 123 125 ). Thus, it might be speculated that, in the absence of preconditioning, when primary cesarean section was performed, AVP administration shortly after birth to the baby, e.g., via nasal spray, might represent a novel strategy to support postnatal adaptation.…”
Section: Avp In Healthy Neonatesmentioning
confidence: 99%
“…After birth, clearing fluid from the lungs to establish sufficient respiration is important. Vasopressin helps to clear pulmonary fluid (8). This indicates that biomarkers representing different physiological actions, such as natriuretic peptides and vasopressin/copeptin, are relevant for sufficient pulmonary function of newborns.…”
Section: Introductionmentioning
confidence: 99%
“…More particularly, there is evidence that AVP itself, which we measured using its surrogate marker copeptin, specifically supports adaptation of the lung, including alveolar fluid reabsorption and surfactant secretion. 21,35,36 In conclusion, oxytocin challenge test-induced contractions suffice to elevate fetal levels of copeptin and inferentially those of AVP. This result is an argument in favor of a trial designed to lower neonatal respiratory morbidity after elective cesarean delivery by a preemptive intervention that increases fetal copeptin levels.…”
Section: Discussionmentioning
confidence: 89%